Evaluasi Program FLS2N (Festival Lomba Seni Siswa Nasional) Di Provinsi DKI Jakarta - Yusnita Sinaga; Iva Sarifah; Dwiutami Wahyuni (SAP (Susunan Artikel Pendidikan), 2025)
This study aims to evaluate the implementation of the National Student Arts Festival (FLS2N) Program in Jakarta Province using a mixed-method approach that combines quantitative and qualitative data in a complementary manner. The evaluation used the CIPP (Context, Input, Process, Product) model to measure the program's relevance, readiness, implementation, and outcomes. Quantitative data were collected through questionnaires distributed to students, supervising teachers, and the organizing committee, while qualitative data were obtained through in-depth interviews, observation, and documentation. The results indicate that the FLS2N program is highly relevant in developing students' artistic potential and preserving local culture. However, several challenges were identified, such as limited equitable access, a lack of ongoing mentoring, and disparities in facilities between schools. Overall, the program's implementation was good, but it still requires strengthening in terms of training management, intersectoral collaboration, and budget optimization. Recommendations from this study include improving resource distribution, increasing the capacity of supervising teachers, and expanding access to participation for students from diverse backgrounds.